Self-Affirmation Through Meditation in The Formation of Self-Concept - Haifa Nurul Anfi, Aura; Balqis Salsabilah, Lady; Khumayah, Siti; Dian Lestari, Aghnia (Matriks Jurnal Sosial dan Sains, 2024)
Thoughts and perspectives ultimately provide the basis for how individuals understand and interpret life experiences. Failure is not the end of a journey but rather an opportunity to grow. This research discusses the process of self-affirmation through meditation to raise awareness of the minds of individuals who experience the lowest point in life, making them feel insecure, stressed, hopeless and losing character. This research uses qualitative methods with the Looking Glass Self theory. In this theory, individuals describe the process by which social reactions and evaluations can have an impact on how we see ourselves. This research aims to gain an in-depth understanding of self-affirmation through meditation in forming self-concept. The results of this research contained 3 findings, namely past trauma and its causes, self-affirmation through meditation, and self-concept. Past trauma is one of the causes for individuals to meditate, for example childhood trauma, breakups and even parental pressure. Self-affirmation through meditation has a positive impact on rising and recovering from failure, so that it can build a positive self-concept by setting boundaries to accept and respect bad social views. This shows that self-affirmation through meditation is an effective way to strengthen self-confidence and create a positive self-concept.